Three-dimensional matrix stiffness-based stem cell soil: Tri-phase biomechanical structure promoted human dental pulp stem cells to achieve pulpodentin regeneration - Xiujuan Li; Yijing Xia; Zhiying Wang; Ziruo Yin; Maotao Weng; Feng Tian; Jie Kang; Yuanjiao Li; Peixuan Ding; Xing Liu; Bin Zhao; Lu Wang (Materials Today Bio)
The regeneration of the pulp-dentine complex is characterized by organizational diversity, with both dentine and pulp being essential for regenerating a complete tooth-like structure. Matrix stiffness plays a crucial role in guiding the multi-lineage differentiation of stem cells during the regeneration process. However, human dental pulp stem cell (HDPSCs) differentiation via three-dimensional (3D) matrix stiffness is still ambiguous. This study employed gelatin methacryloyl hydrogels of varying stiffness to investigate their effects on HDPSCs differentiation, and constructing a Tri-Phase Biomechanical Structure. The effects of 3D stiffness on HDPSCs proliferation, morphology, differentiation, and biomineralization were examined. The underlying mechanisms were analyzed by RNA sequencing (RNA-seq). At the same time, the comprehensive effects of 3D matrix stiffness-induced HDPSCs paracrine signals on periapical cells (endothelial cells, macrophages and fibroblasts) were evaluated. In vitro, high stiffness promoted dentin differentiation, medium stiffness supported vascular differentiation, and low stiffness enhanced vascularization of peri-apical cells through paracrine signals. In vivo, treated dentin matrixes implanted in nude mice further confirmed that this Tri-Phase Biomechanical Structure effectively promoted crownward dentin formation, pulp-like regeneration within root canals, and integration with periapical tissues. These findings highlight that understanding HDPSCs responses to 3D matrix stiffness is crucial for guiding targeted, efficient regeneration of a tooth-like pulpodentin complex.